US-JAPAN INTERNATIONAL SECURITY COOPERATION PROSPECTS - NEMATJONOVA YULDUZ UTKIRJON QIZI; KASIMOV SHAVKAT UROLOVICH; SAMANDAROV MARUF ABDUVAHOB OGLI (International Journal of Innovations in Engineering Research and Technology, 2021)
This article focuses on strategic partnerships and cooperation between Japan and the United States. The article is devoted to the international security of the two countries, in particular, security, stability and integration processes in the international arena. In the article, the two countries say that the alliance between Japan and the United States is a lever for Japanese diplomacy and plays an important role in maintaining stability and prosperity. It was noted that Japan is currently striving to become a major power in the world community, primarily in all-round relations with allied countries. They also touched upon issues such as competition between the United States, Russia and the People's Republic of China, as well as the "rectangular" integration aspirations of new and old economic leaders - Japan, the United States, ASEAN and the People's Republic of China.